Empirical SED templates for star clusters observed with HST and JWST: no strong PAH or IR dust emission after 5 myr - Whitmore, Bradley C.; Chandar, Rupali; Lee, Janice C.; Henny, Kiana F.; Rodríguez, M. Jimena; Baron, Dalya; Bigiel, F.; Boquien, Médéric; Chevance, Mélanie; Chown, Ryan; Dale, Daniel A.; Floyd, Matthew; et al. (The astrophysical journal, 2025)
JWST observations, when combined with Hubble Space Telescope (HST) data, promise to improve age estimates of star clusters in nearby spiral galaxies. However, feedback from young cluster stars pushes out the natal gas and dust, making cluster formation and evolution a challenge to model. Here, we use JWST+ HST observations of the nearby spiral galaxy NGC 628 to produce spectral energy distribution (SED) templates of compact star clusters spanning 275 nm through 21 μm. These preliminary SEDs capture the cluster stars and associated gas and dust within radii of ≈012-067 (corresponding to ≈6-33 pc at the distance of NGC 628). One important finding is that the SEDs of 1, 2, 3, and 4 Myr clusters can be differentiated in the infrared. Another is that, in 80%-90% of the cases we study, the polycyclic aromatic hydrocarbon (PAH) and Hα emission track one another, with the dust responsible for the 3.3 μm PAH emission largely removed by 4 Myr, consistent with pre-supernova stellar feedback acting quickly on the surrounding gas and dust. Nearly embedded cluster candidates have infrared SEDs that are quite similar to optically visible 1-3 Myr clusters. In nearly all cases, we find there is a young star cluster within a few tenths of an arcsec (10-30 pc) of the nearly embedded cluster, suggesting the formation of the cluster was triggered by its presence. The resulting age estimates from the empirical templates are compatible both with dynamical estimates based on CO superbubble expansion velocities, as well as the TODDLERS models, which track spherical evolution of homogeneous gas clouds around young stellar clusters.
Veröffentlicht: 18. März 2025
Gesehen am 09.09.2025